Carbon-Based Nanomaterials 2.0 - Díez-Pascual, Ana María (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint gathers contributions from renowned researchers in the field, offering a collection of the current progress in the preparation, characterization, and applications of carbon-based nanomaterials, including carbon nanotubes, fullerenes, and graphene and its derivatives. The investigation on this type of nanomaterials has increased extraordinarily over the last years owed to their outstanding mechanical, thermal, optical, and electrical properties and superior mechanical properties, have paved the way for a broad range of applications ranging from flexible electronics to biomedicine, bioimaging, and sensing.